2019
DOI: 10.1016/j.heliyon.2019.e01787
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of tempe flour and tofu flour consumption on estrogen serum in ovariectomized rats

Abstract: Estrogen decreasing during menopause can create problems in the cardiovascular organs, brain, urogental tract, and bone. Estrogen replacement therapy (ERT) can be used to increase estrogen levels. However, side-effects including breast cancer may limit their use. Tempe and tofu are natural plat-based foods which contain phytoestrogens. The aim of this research was to compare estrogen serum levels in ovariectomized rats given tempe flour and tofu flour. This research was conducted on female rats, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The analysis results showed that the control group and the OH group had lower estradiol than the IPS and IPTS groups ( Table 2 ). These results are similar to previous studies that there was decrease in serum estrogen in OVx rat aged 12 months compared to non-OVx rat [ 40 ]. Another study showed that serum estradiol decreased in the postmenopause phase [ 2 ].…”
Section: Resultssupporting
confidence: 92%
“…The analysis results showed that the control group and the OH group had lower estradiol than the IPS and IPTS groups ( Table 2 ). These results are similar to previous studies that there was decrease in serum estrogen in OVx rat aged 12 months compared to non-OVx rat [ 40 ]. Another study showed that serum estradiol decreased in the postmenopause phase [ 2 ].…”
Section: Resultssupporting
confidence: 92%
“…It is known that after the cessation of estrogen production by the ovaries, E2 biosynthesis takes place in peripheral tissues, especially adipose tissue, through aromatase conversion of androgens in postmenopausal women (12). Several studies have shown that PEs elevate the levels of E2 in female mice, and BZBS can also increase serum E2 levels (13,14). This is likely because PEs can competitively bind to ERα and ERβ, and the amount of ER in plasma is limited.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely because PEs can competitively bind to ERα and ERβ, and the amount of ER in plasma is limited. Endogenous estrogen cannot bind to the receptor and will be unbound in the plasma, leading to an increase in E2 plasma levels (13,15). As a traditional Chinese medicine, BZBS is composed of a complex molecular mixture and has multi-target effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, tempe has been one of the most consumed protein sources for hundreds of years and known to be more preferable than meat and poultry [ 5 ]. It was reported that the fermentation process during tempe production improved the bioavailability of the protein, fiber, carbohydrates, isoflavones, vitamins [ 6 , 7 , 8 ]. These characteristics have made tempe a healthy protein source for plant-based diets, vegans, and vegetarians [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%